Aphrodisiac activity of ethanolic extract of Pedalium murex Linn fruit - Patel D.K.; Kumar R.; Laloo D.; Sairam K.; Hemalatha S. (My University, 2025)
Objective: The study represents an interesting case report for a very good aphrodisiac activity observed during an oral glucose tolerance test performed while evaluating the antidiabetic potential of Pedalium murex Linn. fruit. Methods: Ethanolic extract of Pedalium murex at a dose of 125, 250 and 500 mg/kg p.o. was given to the rats followed by administration of 2 g/kg p.o. of glucose 30 min after the administration of extract. Results: Pregnancy was observed in the treated groups after 20-25 days of treatment in females which resulted in birth of pubs ranging upto ten in some females (more significant in case of 500 mg/kg p.o.). The observation also showed a significant increase in weights of pubs along with a normal behavior pattern. The increased pregnancy rate in the drug treated groups may be due to the healthy viable sperm and enhancement of sexual desire of the rats. Conclusion: From the results it may be concluded that the fruits of the plant may be used as a good aphrodisiac agent to promote fertility rate. © 2012 Asian Pacific Tropical Biomedical Magazine.